2015
DOI: 10.1016/j.jhevol.2014.10.008
|View full text |Cite
|
Sign up to set email alerts
|

The relevance of the first ribs of the El Sidrón site (Asturias, Spain) for the understanding of the Neandertal thorax

Abstract: The paleobiological significance of the rib cage in Neanderthal ranges from functional anatomy, energetics to the general evolution of human body shape. However, despite this importance there is still debate as to the nature and extent of variations in size and shape of the Neanderthal thorax.The El Sidrón Neanderthals can contribute to this debate providing new thoracic remains (N=245) ranging from fully preserved and undistorted ribs to highly fragmented elements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
46
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 32 publications
4
46
0
1
Order By: Relevance
“…1, 2, 6c) might indicate subtle biomechanical differences in breathing kinematics in Neandertals. Sagittal-cranial orientation of these facets facilitate vertical and oblique gliding movements, allowing for greater medio-lateral expansions , particularly in combination with longer ribs possibly in response to greater diaphragmatic action on central and lower parts of the thorax (T7-T10; Franciscus and Churchill, 2002;Gómez-Olivencia et al, 2009;García-Martínez et al, 2014a;Bastir et al, 2015a). All these aspects are compatible with bio-energetic arguments related to greater muscle and body mass estimates in Neandertals.…”
Section: Discussionsupporting
confidence: 68%
See 4 more Smart Citations
“…1, 2, 6c) might indicate subtle biomechanical differences in breathing kinematics in Neandertals. Sagittal-cranial orientation of these facets facilitate vertical and oblique gliding movements, allowing for greater medio-lateral expansions , particularly in combination with longer ribs possibly in response to greater diaphragmatic action on central and lower parts of the thorax (T7-T10; Franciscus and Churchill, 2002;Gómez-Olivencia et al, 2009;García-Martínez et al, 2014a;Bastir et al, 2015a). All these aspects are compatible with bio-energetic arguments related to greater muscle and body mass estimates in Neandertals.…”
Section: Discussionsupporting
confidence: 68%
“…With respect to the El Sidrón fossils, the analysis of centroid size (Fig. 4) supports an assignment of SD-1619 to a young (and not so large) adult and of SD-1641 to In a more general morphological framework, the current study addressed the hypothesis that the enlarged thorax of Neandertals is not only the result of larger ribs (Franciscus and Churchill, 2002;Gómez-Olivencia et al, 2009;García-Martínez et al, 2014a, Bastir et al, 2015a, but also of a more dorsal orientation of the transverse processes of the thoracic vertebrae (Bastir et al, 2015b). A similar kind of influence of vertebral shape on rib cage morphology has been proposed in Australopithecus (Ward et al, 2012) and Homo ergaster/erectus (Jellema et al, 1993;Latimer and Ward, 1993), and more recently also identified as a geometric feature of modern human sexual dimorphism García-Martínez et al, 2016a).…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations